Effectiveness of Video Games as Physical Treatment in Patients with Cystic Fibrosis: Systematic Review - Remedios López-Liria; Daniel Checa-Mayordomo; Francisco Antonio Vega-Ramírez; Amelia Victoria García-Luengo; María Ángeles Valverde-Martínez; Patricia Rocamora-Pérez (Sensors, 2022)
Physical training at home by making individuals play active video games is a new therapeutic strategy to improve the condition of patients with cystic fibrosis (CF). We reviewed studies on the use of video games and their benefits in the treatment of CF. We conducted a systematic review with data from six databases (PubMed, Medline, Scopus, Web of Science, PEDro, and Cochrane library plus) since 2010, according to PRISMA standards. The descriptors were: “Cystic Fibrosis”, “Video Game”, “Gaming Console”, “Pulmonary Rehabilitation”, “Physiotherapy”, and “Physical Therapy”. Nine articles with 320 participants met the inclusion criteria and the study objective. Patients who played active video games showed a high intensity of exercise and higher ventilatory and aerobic capacity compared to the values of these parameters in tests such as the cardiopulmonary stress test or the six-minute walk test. Adequate values of metabolic demand in these patients were recorded after playing certain video games. A high level of treatment adherence and satisfaction was observed in both children and adults. Although the quality of the included studies was moderate, the evidence to confirm these results was insufficient. More robust studies are needed, including those on evaluation and health economics, to determine the effectiveness of the treatment.